Global Studies of Using Fecal Biomarkers in Predicting Relapse in Inflammatory Bowel Disease - Liu, Fang; Lee, Seul A.; Riordan, Stephen M.; Zhang, Li; Zhu, Lixin (Frontiers in Medicine, 2020)
Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract mainly comprising two forms including Crohn's disease (CD) and ulcerative colitis (UC). IBD is a lifelong relapsing remitting disease and relapses occur at random patterns which are unpredictable. Fecal biomarkers have been increasingly used to assess disease activity in IBD due to their positive correlations with intestinal inflammation. Recent studies have also assessed the use of fecal biomarkers in predicting relapse and post-operative recurrence. This review provides information from global studies of using fecal calprotectin, lactoferrin and S100A12 to predict relapse in IBD. Strategies for further studies and the use of these fecal biomarkers for personalized management in IBD are also discussed.